Diverging scaling with converging multisite entanglement in odd and even quantum Heisenberg ladders - Sudipto Singha Roy; Himadri Shekhar Dhar; Debraj Rakshit; Aditi Sen(De); Ujjwal Sen (New Journal of Physics, 2016)
We investigate finite-size scaling of genuine multisite entanglement in the ground state of quantum spin-1/2 Heisenberg ladders. We obtain the ground states of odd- and even-legged Heisenberg ladder Hamiltonians and compute genuine multisite entanglement, the generalized geometric measure (GGM), which shows that for even rungs, GGM increases for odd-legged ladder while it decreases for even ones. Interestingly, the ground state obtained by short-range dimer coverings, under the resonating valence bond ansatz, encapsulates the qualitative features of GGM for both the ladders. We find that while the quantity converges to a single value for higher legged odd- and even-ladders, in the asymptotic limit of a large number of rungs, the finite-size scaling exponents of the same tend to diverge. The scaling exponent of GGM is therefore capable to distinguish the odd–even dichotomy in Heisenberg ladders, even when the corresponding multisite entanglements merge.